(untitled) (Ustozlar uchun, 2025)
Annotation. This article offers an in-depth examination of the distinctive authorial style and the role of imagery in O. Henry’s short stories. Widely known for his sharp wit, ironic twists, and unexpected conclusions, O. Henry has solidified his reputation as one of the most prominent short story writers in American literature. The article explores how his stylistic choices, including his simple yet effective prose, humorous tone, and emotional depth, serve to captivate readers and elevate the impact of his stories. The analysis delves into his masterful use of imagery, where his vivid and detailed descriptions create dynamic settings, evoke emotional responses, and help bring his characters to life [1]. By focusing on a selection of his most renowned works, the study illustrates how O. Henry’s use of imagery intertwines with his storytelling techniques to enhance the themes of social justice, human kindness, and the complexities of human nature. This exploration provides insight into the creative process behind O. Henry’s works, shedding light on how his style and imagery contribute to the timeless appeal of his stories, which continue to resonate with readers across generations.